Maternal antioxidant intake during pregnancy and the development of cows' milk allergy in the offspring. Issue 12 (28th June 2021) - Tuokkola, Jetta; Lamminsalo, Anni; Metsälä, Johanna; Takkinen, Hanna-Mari; Tapanainen, Heli; Åkerlund, Mari; Niinistö, Sari; Toppari, Jorma; Ilonen, Jorma; Veijola, Riitta; Knip, Mikael; Kaila, Minna; et al.
Abstract: Cows' milk allergy (CMA) is the most common food allergy in young children, and it is often the first manifestation of atopic diseases. Accordingly, very early environmental factors, such as maternal diet during pregnancy, may play a role in the development of CMA, but the evidence is limited. The aim of this study was to investigate the association between maternal intake of antioxidant nutrients during pregnancy and the subsequent development of CMA in the offspring in a prospective, population-based birth cohort within the Finnish Type 1 Diabetes Prediction and Prevention Study. Maternal dietary information during pregnancy was collected with a detailed, validated FFQ. The maternal dietary information and the information on putative confounding factors were available for 4403 children. Information on diagnosed CMA ( n 448) was obtained from a medical registry and queried from the parents up to child's age of 3 years. The Finnish food composition database was used to calculate the average daily intake of nutrients. Logistic regression was applied for statistical analyses, and the nutrient intakes were adjusted for energy intake. OR are presented per 1 sd increment of the particular nutrient intake. Maternal total and dietary intake of β -carotene was associated with an increased risk of CMA in the offspring when adjusted for the putative confounding factors (total OR 1·10, 95 % CI 1·02, 1·20; dietary OR 1·10; 95 % CI 1·01, 1·19). Using dietary supplements containing antioxidants in addition to a balanced diet may not confer any additional benefits.